Literacy Culture as a Reinforcement of Tolerance Character Through The Stories of Prophet Muhammad SAW : an Effort to Promote Religious Moderation at The Level of Elementary School - Fauziah, Giska Enny Fauziah; Aliyah, Nafilah Na’imatul (Proceedings of Annual Conference for Muslim Scholars, 2023)
Literacy programs is a crucial movement education, particularly at the level of elementary school. By reading we gaining new knowledge. Literacy culture can be an effort to strengthen the character of tolerance, especially through stories of the Prophet Muhammad SAW. The life stories of Prophet Muhammad SAW offer valuable insights into core values such as mutual respect, honor, and understanding. These stories can be studied through various media, such as books, stories and films. Religious moderation, involving a balanced understanding and practice of faith, is an integral aspect of character development. The promotion of tolerance character through literacy initiatives becomes a key facilitator in achieving this goal. This research adopts the literature research. This Method to comprehensively explore emerging phenomena. The research process entails collecting data and information from diverse sources, including books, journals, notes, articles, and other relevant materials related to the subject under investigation. The research findings indicate that : at the elementary school level, the implementation of literacy programs, such as the “Gerakan Literasi Sekolah” (GLS), encompasses activities like reading and analyzing the stories of Prophet Muhammad SAW. Additionally, students engage in watching films or videos portraying the life of Prophet Muhammad SAW, enabling them to extract value lessons and emulate his character, particularly in interactions with Nasrani and the Quraishy community. Efforts to fortify tolerance character through literacy culture play a pivotal role in helping students internalize and apply these values in their daily lives. This initiative is paramount for fostering a harmonious and peaceful societal coexistence.